PENGARUH NILAI INTERNAL INDIVIDU TERHADAP SENJANGAN ANGGARAN PADA INSTANSI PEMERINTAH DI WILAYAH BAYAR KANTOR PELAYANAN PERBENDAHARAAN NEGARA DUMAI - Raditya Yudhan Kustanto (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to empirically analyze and assess the effect of the individual internal values consisting of achievement, power, and tradition on the propensity of budgetary slack in public sector organizations. The sample of this quantitative research is treasurers and treasury management officers in governmental agencies in the pay-service area of KPPN Dumai. The hypothesis of this study were tested using multiple regression analysis. The results show that the achievement and power values have a positive and significant effect on the propensity of budgetary slack. The finding indicates that the higher the achievement and power value of a person, the higher his budgetary slack propensity level. Meanwhile, tradition value has a negative and significant influence on the propensity of budgetary slack. This suggests that individual tradition value must be increased to lower his budgetary slack propensity level. The findings imply that cultivating values and ethical norms of employees is necessary to increase their moral judgment, so they see budgetary slack as a moral hazard behavior. Keywords: individual internal value, public sector budgeting, budgetary slack